Trust in Social Commerce: Insights from a Bibliometric Review and BERTopic Topic Modelling Analysis - Shao, Yang; Rosli, Nadzirah; Hashim, Sharizal (International Review of Management and Marketing, 2026)
This study integrates bibliometric analysis and BERTopic topic modelling to systematically examine the development and thematic structure of trust research in social commerce. Following the SPAR-4-SLR protocol, this study analyses 1,055 publications retrieved from Web of Science and Scopus spanning from 2005 to May 2026. Bibliometric analysis maps the publication trends, influential contributors, key journals, and institutional concentrations of trust research in social commerce. BERTopic analysis identifies 13 distinct research themes and traces their evolution over two decades. Building on these findings, an integrative framework is proposed that positions three types of trust as the central construct, shaped by five antecedent dimensions (technology, business, social, information, and consumer), leading to three behavioural outcomes (social commerce adoption, impulsive buying behaviour, and technology acceptance), moderated by cultural differences, and contextualized within live streaming commerce and COVID-19. The study offers a structured synthesis of trust research in social commerce and identifies directions for future inquiry.